Serum Cystatin C Level in Liver Cirrhosis Patients with MELD-Na > 22 - Arnelis Arnelis; Vesri Yoga; Nasrul Zubir; Saptino Miro; Andry Kurniawan (The Indonesian Society for Digestive Endoscopy, 2022)
Background: Hepatorenal syndrome is a part of the prerenal acute kidney injury (AKI) characterized by kidney dysfunction which is secondary to the decreased renal blood flow that occurs in liver cirrhosis with portal hypertension and is a fatal complication. Hepatorenal syndrome (HRS) occurs in about 20% of liver cirrhosis patients with refractory ascites.Method: This study was conducted on 24 liver cirrhosis patients with ascites who visited Gastroenterohepatology Outpatient Ward and Internal Medicine Inpatient Unit, Dr. M. Djamil Padang. Samples were collected and data analyses were conducted in December 2019 to March 2020.Results: In this study, the model for end-stage liver disease (MELD)-Na score was used to determine the risk of HRS in liver cirrhosis patients with ascites, in which patients with a MELD-Na score 22 belonged to the group at risk of developing HRS. From 24 patients, the mean MELD-Na score was 24.58 ± 3.5. The lowest MELD-Na score was 22 in 8 patients (33.3%), while 1 patient (4.2%) had the highest MELD-Na score of 35. In this study, serum CysC levels were measured in patients with normal creatinine, and the mean serum CysC level was 2.69 ± 0.46 mg/L. The minimum value of CysC was 2.03 mg/L, while the maximum value was 3.9 mg/L. Serum CysC levels in all 24 patients were increased compared to the normal values.Conclusion: Liver cirrhosis patients who were at risk to develop HRS based on the MELD-Na score have increased serum Cystatin C levels, although serum creatinine levels were still normal.